Environmental Policy Shocks and Manufacturing Resilience: A Multi-Path Mechanism and Regional Heterogeneity Analysis - Yao, Xingyuan; Wang, Zheqiu; Zheng, Kangze; Lin, Qingfan; Lin, Weiming; Zhong, Yufen (Sustainability, 2025)
Environmental regulation has become a central policy tool for reconciling the tensions between ecological sustainability and industrial development. Although most existing studies focus on its impact on green innovation or firm behavioral change, attention to how environmental regulation affects the structural resilience of manufacturing systems under external shocks remains limited. This paper constructs a balanced panel dataset covering 287 prefecture-level cities in mainland China from 2006 to 2021 to quantify the impact of environmental regulation intensity on the resilience of manufacturing development. Manufacturing resilience is assessed through a comprehensive indicator system, including the dimensions of adaptive capacity, recovery potential, and industrial continuity. The empirical results show that environmental regulation has a significant inhibitory effect on manufacturing resilience, and this effect is supported in a number of robustness analyses using instrumental variable estimation and lagged structural tests. Mechanism analysis suggests that, despite the overall negative effect, environmental regulations can indirectly enhance resilience performance by promoting industrial autonomy and digital transformation under certain conditions. Heterogeneity analysis further reveals that the negative effect is more pronounced in regions with higher regulatory intensity, in non-self-employed firms, in industries not subject to U.S. sanctions, and in eastern China. These findings suggest that the dynamic needs of the industrial system should be taken into account in the formulation of environmental policies, and that digital capacity building and autonomy upgrading should be the key paths to mitigate regulatory shocks.